2020
DOI: 10.1101/2020.12.23.20248683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the usage of indirect motor pathways following a hemiparetic stroke

Abstract: A hallmark impairment in a hemiparetic stroke is a loss of independent joint control resulting in abnormal co-activation of shoulder abductor and elbow flexor muscles in their paretic arm, clinically known as the flexion synergy. The flexion synergy appears while generating shoulder abduction (SABD) torques as lifting the paretic arm. This likely be caused by an increased reliance on contralesional indirect motor pathways following damage to direct corticospinal projections. The assessment of functional connec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…This reorganization is likely due to the increased recruitment of ipsilateral cortical regions during the processing of the somatosensory signals from the paretic hand. This is consistent with neuroimaging studies that have demonstrated increased ipsilateral cortical sensorimotor activity during movement [6][7][8]34], which may require the sensory signal to re-route to provide sensory feedback for ipsilateral motor control.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This reorganization is likely due to the increased recruitment of ipsilateral cortical regions during the processing of the somatosensory signals from the paretic hand. This is consistent with neuroimaging studies that have demonstrated increased ipsilateral cortical sensorimotor activity during movement [6][7][8]34], which may require the sensory signal to re-route to provide sensory feedback for ipsilateral motor control.…”
Section: Discussionsupporting
confidence: 90%
“…ERP voltage maps were calculated and drawn at the mean latency of each component. The standardized low-resolution electromagnetic tomographic analysis, sLORETA (v20200701) was used to localize the ERP source activity on the cortex [27,28] The laterality index was computed to investigate the hemisphere dominance of cortical response in the time window of the P50-N100 [29,30]. The LI is defined as the signal power difference between contralateral and ipsilateral hemispheres in the sensorimotor areas (including C1/2, C3/4, C5/6, CP1/2, CP3/4, CP5/6 in 10/20 EEG recording system) and then normalized by their sum, as shown in the equation below.…”
Section: Figure 1 Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In real applications, different numerical values could be used based on real experimental data. For example, we applied M-PLV to check 1:1 (integer) and 2:1 (1/2 non-integer) coupling and estimated delay between electroencephalography (EEG) and electromyography (EMG) signals during a motor task to demonstrate a real application of M-PLV (see Section III C), where the numerical values are from the real data obtained in a human subject experiment [23].…”
Section: Methodsmentioning
confidence: 99%
“…We tested M-PLV on two scenarios where synthetic coupled signals are generated using white Gaussian signals, and a system comprised of multiple coupled Rössler oscillators. The real application of M-PLV was demonstrated in a EEG-EMG data dataset recorded from human subjects during a motor task [23].…”
Section: Introductionmentioning
confidence: 99%